Sepsis in tropical regions: Report from the task force on tropical diseases by the World Federation of Societies of Intensive and Critical Care Medicine - McGloughlin, Steve; Richards, Guy A.; Mat Nor, Mohd Basri; Prayag, Shirish; Baker, Tim; Amin, Pravin R. (Elsevier, 2018)
Sepsis and septic shock in the tropics are caused by a wide array of organisms. These infections are encountered mainly in low and middle-income countries (LMIC) where a lack of infrastructure and medical facilities contribute to the high morbidity and mortality. Published sepsis guidelines are based on studies primarily performed in high income countries and as such recommendations may or may not be relevant to practice in the tropics. Failure to adhere to guidelines, particularly among non-intensive care specialists even in high-income countries, is an area of concern for sepsis management. Additionally, inappropriate use of antimicrobials has led to significant antimicrobial resistance. Access to rapid, low-cost, and accurate diagnostic tests is critical in countries where tropical diseases are prevalent to facilitate early diagnosis and treatment. Implementation of performance improvement programs may improve outcomes for patients with sepsis and the addition of resuscitation and treatment bundles may further reduce mortality. Associated co-morbidities such as malnutrition and HIV influence outcomes and must be considered.